The Severity of the COVID-19 Among Chronic Disease Patients in the Selected Hospitals in Riyadh, Saudi Arabia – A Retrospective Study [Corrigendum] - Al-Rawi MBA; Khan AHI; Sheikh Ghadzi SM (Risk Management and Healthcare Policy)
Al-Rawi MBA, Khan AHI, Sheikh Ghadzi SM. Risk Manag Healthc Policy. 2024;17:3327—3339. The authors have advised there is an error in the author list on page 3327. The author name “Amer Hayat Ibrahim Khan” should read “Amer Hayat Khan”.